Polyethylene resin composition for biaxially oriented film

The problems of biaxially extended strength and temperature range are solved by using polyethylene resin compositions with specific graded characteristics in biaxially oriented films, including ultra-low density, linear low density and high density copolymers, and excellent extension characteristics are achieved and smoothness, suitable for a wider range of applications.

CN119301189APending Publication Date: 2025-01-10LOTTE CHEM CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380042697.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-27
Filing Date
2023-02-22
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing biaxially oriented films are difficult to obtain satisfactory strength characteristics when biaxially extending, and have insufficient extension performance over a wider temperature range, making it difficult to achieve single materialization.

Method used

The polyethylene resin composition fractionated by a-TREF analysis includes 1 to 30% ultra-low density copolymer A, 60 to 98% linear low density copolymer B, and 1 to 10% high density copolymer C. , the molding is carried out by cross-grade chromatography to ensure that the molecular weight distribution of the resin composition below 35°C and above 94°C is within a range of 5 to 20%, the melt flow index and density are within a specific range, and the excellent ductility and smoothness are achieved. Spend.

Benefits of technology

Achieve biaxial extension in a wider temperature range, with longitudinal and transverse tensile strengths reaching more than 700kgf/cm2, with a thickness deviation of less than 15%, haze less than 10%, and keeping the thickness of the film smooth over a wider temperature range Excellent degree and transparency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301189A_ABST
    Figure CN119301189A_ABST
Patent Text Reader

Abstract

Disclosed is a polyethylene resin composition for a biaxially oriented film, which can be molded by a biaxial extension machine, exhibits excellent extension characteristics, can be biaxially extended over a wider temperature range, and has excellent thickness smoothness and transparency. The present invention provides a polyethylene resin composition for a biaxially oriented film in which the molecular weight of a substance classified at a temperature of 35 DEG C or less is 5 to 20 wt% and the molecular weight of a substance classified at a temperature of 94 DEG C or more is 5 to 20 wt% by an a-TREF (Analytical Tempering Element Fractionation) analysis, and the polyethylene resin composition for a biaxially oriented film in which the molecular weight of a substance classified at a temperature of 94 DEG C or more is 5 to 20 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyethylene resin composition, and more particularly to a polyethylene resin composition for a biaxially oriented film. Background Art

[0002] For the plastics-related industries, the market environment is undergoing a dramatic change as new issues, including the marine plastics problem, emerge. Container packaging materials, which are used in large quantities, are no exception. Not only in the production of packaging materials, but also in the fields of food / beverage processing and distribution, environmental issues such as plastic waste and greenhouse gas emissions are being addressed.

[0003] In particular, packaging container companies are aware of the need to focus on developing materials that can reduce environmental burdens, and are developing and using single-material products and products that contribute to reducing carbon dioxide emissions (CO2) on a global scale based on recycling. 2 )’s bioplastics are becoming increasingly active.

[0004] Polyethylene (PE) materials have become the mainstream of the trend of single materialization worldwide. This is because in the design process of multi-layer films, the silane layer is first discussed in consideration of the content and purpose, and the proportion of polyethylene used in the middle silane layer is relatively high. When the entire product is made of a single material, the surface material is also likely to use polyethylene in the end.

[0005] In the United States, since the recovery and recycling mechanism of polyethylene products has been established, the supply of polyethylene is expected to dominate. Mitsui Chemicals, which has raw material resin manufacturers and film manufacturers, is committed to the single material of polyethylene with the goal of replacing nylon / polyethylene structures. In addition, Dow Chemical is replacing the soft packaging materials used in film applications with too many functions (dried fruits, frozen foods, pet food, etc.) from PET / PE to PE single (Uni) material (single product).

[0006] In addition, for biaxially oriented films, when BOPE (biaxially oriented polyethylene) replaces the layer previously used with BOPA (biaxially oriented polyamide) or BOPET (biaxially oriented polyethylene terephthalate) to achieve a single material, it may be in line with this development trend, but to date there has been no example of polyethylene that can be molded using a biaxial stretching machine and exhibits satisfactory stretching characteristics.

[0007] Korean Patent No. 0746253 discloses a polyethylene-based stretched film having excellent Elmendorf tear strength and uniform stretchability, but it is difficult to obtain satisfactory strength characteristics when the proposed composition is actually used for biaxial stretching. Summary of the invention

[0008] The object of the present invention is to provide a polyethylene resin composition for a biaxially oriented film, which can be formed by a biaxial stretching machine and exhibits excellent stretching characteristics, can be biaxially stretched in a wider temperature range, and has excellent thickness smoothness and transparency.

[0009] In order to solve the above-mentioned problems, the present invention provides a polyethylene resin composition for biaxially oriented films, which, through a-TREF (Analytical Temperature rising elution fractionation) analysis, has a molecular weight of 5 to 20 weight % of a substance fractionated at a temperature below 35°C, and a molecular weight of 5 to 20 weight % of a substance fractionated at a temperature above 94°C.

[0010] Furthermore, a polyethylene resin composition for a biaxially oriented film is provided, characterized in that the resin composition comprises: 1 to 30 weight percent of a copolymer A, wherein the copolymer A is a copolymer of ethylene and an olefin having 4 to 10 carbon atoms, and has a density of 0.860 to 0.910 g / cm 3 ; 60 to 98% by weight of copolymer B, wherein copolymer B is a copolymer of ethylene and an olefin having 4 to 10 carbon atoms and a density of 0.925 g / cm 3 Above and less than 0.940g / cm 3 and 1 to 10% by weight of a copolymer C, wherein the copolymer C is a copolymer of ethylene and an olefin having 4 to 10 carbon atoms and a density of 0.940 to 0.970 g / cm 3 .

[0011] Furthermore, a polyethylene resin composition for a biaxially oriented film is provided, characterized in that, through a-TREF (Analytical Temperature rising elution fractionation) analysis, the molecular weight of a substance fractionated at a temperature below 35°C is 5 to 20 weight %, and the molecular weight of a substance fractionated at a temperature above 94°C is 5 to 20 weight %.

[0012] In addition, a polyethylene resin composition for biaxially oriented film is provided, characterized in that the melt flow index (190°C, 2.16 kg load) of the copolymer A is 0.2 to 6 g / 10 min, the melt flow index (190°C, 2.16 kg load) of the copolymer B is 1 to 3.5 g / 10 min, and the melt flow index (190°C, 2.16 kg load) of the copolymer C is 0.2 to 2.5 g / 10 min.

[0013] Furthermore, a polyethylene resin composition for biaxially oriented films is provided, characterized in that the glass transition temperature (Tg) of the copolymer A is -50 to -45°C, the melting point (Tm) of the copolymer B is 120 to 130°C and the crystallization temperature (Tc) is 110 to 115°C, and the melting point (Tm) of the copolymer C is 130 to 140°C and the crystallization temperature (Tc) is 115 to 125°C.

[0014] Furthermore, a polyethylene resin composition for a biaxially oriented film is provided, wherein the resin composition has a melt flow index (190°C, 2.16 kg load) of 1 to 3 g / 10 min and a density of 0.920 to 0.940 g / cm 3 .

[0015] Furthermore, a polyethylene resin composition for a biaxially oriented film is provided, wherein the longitudinal and transverse tensile strengths of the resin composition measured under the following conditions are 700 kgf / cm 2 Above, the extension thickness deviation is less than 15%, and the haze is less than 10%.

[0016] [Measurement method]

[0017] A biaxially stretched film having a film thickness of 20 μm and a film width of 8 m was prepared using the resin composition under the conditions of a molding speed of 400 m / min, a five-fold longitudinal (MD) elongation and a stretching temperature of 112 to 128° C., a nine-fold transverse elongation and a stretching temperature of 108 to 116° C., and the tensile strength of the test piece of the biaxially stretched film was measured using a tensile tester (model name: Instron, 4466) under the conditions of a load cell of 100 N and a test speed of 500 mm / min according to the provisions of ASTM D882, the prepared film was cut into a length of 1 m, and the thickness was measured at any one of the eight equal parts, the thickness deviation compared to before stretching was calculated, and the average value of the thickness deviation was taken to measure the stretched thickness deviation, and the test piece was measured using a haze meter (model name: Nippon) according to the provisions of ASTM D1003. The haze of the stretched film was measured by Denshoku (NDH5000).

[0018] According to the present invention, a polyethylene resin composition can be provided, which is a polyethylene resin composition obtained by mixing three copolymers of ethylene and an olefin having 4 to 10 carbon atoms with different densities in a prescribed range, and further has specific classification characteristics when a-TREF analysis is performed using CFC, thereby providing a polyethylene resin composition that can be molded by a biaxial stretching machine and exhibits excellent stretching characteristics, can be biaxially stretched in a wider temperature range, and has excellent thickness smoothness and transparency. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a conceptual diagram for explaining the TREF analysis method for a resin composition in the present invention.

[0020] Figure 2 and Figure 3 Each of the graphs shows a temperature-elution fractionation curve obtained by analyzing the compositions prepared in Example 1 and Comparative Example 1 by temperature-elution fractionation using TREF. DETAILED DESCRIPTION

[0021] The present invention is described in detail below through preferred embodiments. Prior to this, the terms or words used in this specification and claims shall not be interpreted in the usual or dictionary meanings. Based on the principle that the inventor can appropriately define the concept of terms in order to describe his invention in the best way, these terms or words should be interpreted as meanings and concepts that conform to the technical ideas of the present invention. Therefore, the structure of the embodiment recorded in this specification is only the best embodiment of the present invention and does not represent all the technical ideas of the present invention. Therefore, it should be understood that various equivalents and variations that can replace the embodiments may be present when this application is filed.

[0022] In the case that a composition showing satisfactory ductility has not been proposed when a layer previously used with BOPA or BOPET is replaced with BOPE to achieve a single material, the inventors have found that the following polyethylene resin composition can be molded by a biaxial stretching machine and shows excellent ductility, and can be biaxially stretched in a wider temperature range, and has excellent thickness smoothness and transparency, and have proposed the present invention. The polyethylene resin composition is a polyethylene resin composition having a specific fractionation characteristic when performing a-TREF analysis using CFC (Cross-Fractionation Chromatography), and is a copolymer of three types of ethylene and an olefin having 4 to 10 carbon atoms with different densities mixed in a specified range.

[0023] Therefore, the present invention discloses a polyethylene resin composition for biaxially oriented film, wherein the molecular weight of the material fractionated at a temperature below 35°C is 5-20% by weight and the molecular weight of the material fractionated at a temperature above 94°C is 5-20% by weight by a-TREF (Analytical Temperature rising elution fractionation) analysis. The resin composition of the present invention preferably comprises: 1-30% by weight of a copolymer A, wherein the copolymer A is a copolymer of ethylene and an olefin having 4 to 10 carbon atoms, and has a density of 0.860-0.910 g / cm 3 ; 60 to 98% by weight of copolymer B, wherein copolymer B is a copolymer of ethylene and an olefin having 4 to 10 carbon atoms and a density of 0.925 g / cm 3 Above and less than 0.940g / cm 3 and 1 to 10% by weight of a copolymer C, wherein the copolymer C is a copolymer of ethylene and an olefin having 4 to 10 carbon atoms and a density of 0.940 to 0.970 g / cm 3 .

[0024] In the present invention, the copolymer A may be ultra-low density polyethylene, and its density may be 0.860-0.910 g / cm 3 , preferably 0.870~0.910g / cm 3 When the density exceeds the above range, biaxial stretch molding is difficult.

[0025] Furthermore, the glass transition temperature of the copolymer A is preferably -40° C. or lower, and more preferably -50 to -40° C. In this case, it is possible to prevent the physical properties of the final film from being degraded when used in a low-temperature environment.

[0026] Moreover, for the copolymer A, a copolymer prepared using a metallocene catalyst can be preferably used, a copolymer of ethylene and α-olefins such as 1-butene, 1-hexene, and 1-octene can be used, preferably a copolymer of ethylene and α-olefins having 6 to 8 carbon atoms can be used, and more preferably a copolymer of ethylene and 1-hexene or 1-octene can be used. Moreover, the melt flow index (190°C, 2.16kg load) can be 0.2 to 6g / 10min, preferably 0.5 to 2g / 10min. When a copolymer prepared using a Ziegler-Natta catalyst is applied, or a copolymer prepared using α-olefins other than 4 to 10 carbon atoms as a comonomer copolymerized with ethylene, or when the melt flow index exceeds the range, it may also be difficult to perform biaxial stretch molding. The polymerization method of copolymer A is not particularly limited and can be prepared by any method such as a gas phase method, a solution method, a slurry method, etc.

[0027] In the overall resin composition, the copolymer A may be included in an amount of 1 to 30% by weight, preferably 10 to 30% by weight. When the content of the copolymer A exceeds the range, biaxial stretch molding is difficult, and when it exceeds 30% by weight, the mechanical properties decrease due to a large amount of low-crystalline molecules, resulting in a decrease in the final tensile strength.

[0028] In the present invention, the copolymer B may be a linear low-density polyethylene with a density of 0.925 to 0.940 g / cm 3 , preferably 0.925 to 0.935 g / cm 3 When the density exceeds the above range, biaxial stretch molding is difficult.

[0029] Moreover, for the copolymer B, a copolymer prepared using a Ziegler-Natta catalyst can be preferably used to ensure the range of the moldable film, and a copolymer of ethylene and α-olefins such as 1-butene, 1-hexene, and 1-octene can be used, preferably a copolymer of ethylene and 1-butene, 1-hexene or 1-octene can be used, and the melt flow index (190°C, 2.16kg load) can be 1 to 3.5g / 10min, preferably 2 to 3g / 10min. When a copolymer prepared using a metallocene catalyst is applied, or a copolymer prepared using an α-olefin other than 4 to 10 carbon atoms as a comonomer copolymerized with ethylene, or when the melt flow index exceeds the range, it is also possible that biaxial stretch molding is difficult. The polymerization method of copolymer B is not particularly limited and can be prepared by any method such as a gas phase method, a solution method, a slurry method, etc.

[0030] Moreover, the melting point of the copolymer B is preferably 120-130°C and the crystallization temperature is 110-115°C, so that the final film can be biaxially stretched in a wider temperature range, thereby being biaxially stretched in a wider stretching process temperature range of 108-128°C.

[0031] In the overall resin composition, the copolymer B may be included in an amount of 60 to 98 wt %, preferably 65 to 80 wt %. When the content of the copolymer B exceeds the range, biaxial stretch molding is difficult, and when it is less than 60 wt %, the tensile strength of the film is significantly reduced.

[0032] In the present invention, the copolymer C may be a high-density polyethylene mixed in order to increase the tensile strength of the final film and improve the ductility, processability and color, and the density may be 0.940 to 0.970 g / cm 3 , preferably 0.950 to 0.960 g / cm 3 When the density exceeds the above range, biaxial stretch molding is difficult.

[0033] Moreover, for the copolymer C, a copolymer of ethylene and α-olefins such as 1-butene, 1-hexene, 1-octene, etc. can be used, preferably a copolymer of ethylene and 1-butene or 1-hexene can be used, and the melt flow index (190°C, 2.16kg load) can be 0.2 to 2.5g / 10min, preferably 0.2 to 1g / 10min. When an α-olefin other than 4 to 10 carbon atoms is used as a comonomer for copolymerization with ethylene to prepare the copolymer, or when the melt flow index exceeds the range, it may also be difficult to perform biaxial stretch molding. The polymerization method of copolymer C is not particularly limited, and it can be prepared by any method such as a gas phase method, a solution method, a slurry method, etc.

[0034] Moreover, in order to maintain the rigidity of the film during the stretching process to further improve the formability and maximize the mechanical properties of the final biaxially stretched film, the melting point of the copolymer C is preferably above 130°C, more preferably 130-140°C, and the crystallization temperature may be 115-125°C.

[0035] In the overall resin composition, the copolymer C may be included in an amount of 1 to 10 wt %, preferably 3 to 10 wt %. When the content of the copolymer C exceeds 10 wt %, the copolymer may not be extended during the extension process due to a large amount of crystalline molecules, resulting in fracture.

[0036] By mixing the copolymer A, copolymer B and copolymer C as described above, the melt flow index (190°C, 2.16 kg load) of the final resin composition can be 1 to 3 g / 10 min, preferably 1.5 to 2.5 g / 10 min, and the density can be 0.900 to 0.940 g / cm 3 , preferably 0.925 to 0.935 g / cm 3 .

[0037] It has been confirmed that when the polyethylene resin composition of the above composition is molded into a biaxially oriented film in the present invention, when a-TREF (Analytical Temperature rising elution fractionation) analysis is performed using CFC (Cross-Fractionation Chromatography) and has a predetermined fractionation characteristic, smooth moldability is exhibited, satisfactory strength characteristics are achieved, biaxial stretching can be performed in a wider temperature range, and thickness smoothness and transparency are improved. Specifically, as described above, the resin composition of the present invention can have a molecular weight of 5 to 20% by weight at a temperature fractionation of 35°C or less, and a molecular weight of 5 to 20% by weight at a temperature fractionation of 94°C or more, preferably a molecular weight of 10 to 20% by weight at a temperature fractionation of 35°C or less, and a molecular weight of 5 to 15% by weight at a temperature fractionation of 94°C or more.

[0038] The temperature-molecular weight curve obtained by the a-TREF analysis method in the present invention is based on Flory Huggins' statistical thermodynamics formula (see the following mathematical formula 1) which is a temperature rising elution fractionation method and represents the phenomenon that the melting point decreases due to a diluent.

[0039] [Mathematical formula 1]

[0040]

[0041] In mathematical formula 1, T m is the melting point of pure polymer, T m 0 is the melting point of the diluted polymer, R is the gas constant, ΔH u is the melting heat per repeating unit of the polymer, N A is the mole fraction of the diluent.

[0042] Solvents or comonomers can be considered as diluents for polymers, and the crystallization temperature of polyolefins can decrease with the increase of diluent concentration. In TREF experiments, after melting the sample and injecting it into the column at high temperature, the temperature needs to be slowly lowered to guide the crystallization of the sample. After lowering the temperature to allow the polymer to precipitate in the column, the column temperature is slowly raised again according to the heating process. The sample dissolved according to the temperature of the polymer precipitated in the column is analyzed, and the molecular weight of the substances dissolved at each temperature is distinguished (refer to Figure 1 ).

[0043] In order to be applied to various purposes, conventional polyethylene additives may be added to the polyethylene resin composition for biaxially oriented films of the present invention, for example, appropriate amounts of antioxidants, heat stabilizers and light stabilizers, antistatic agents, lubricants, anti-caking agents, preservatives, processing aids, slip agents, anti-sticking agents, pigments, flame retardants, foaming agents, etc. may be added for use.

[0044] The polyethylene resin composition for biaxially oriented films of the present invention can be prepared by mixing and extruding the above components according to conventional methods known in the art. For example, the above components can be put into a biaxial extruder and melt-kneaded to prepare the polyethylene resin composition for biaxially oriented films.

[0045] The polyethylene resin composition for biaxially oriented film of the present invention can be biaxially stretched and molded, and exhibits excellent stretching properties. Specifically, the longitudinal and transverse tensile strengths measured under the following conditions can be 700 kgf / cm 2 The transverse tensile strength is preferably 950 kgf / cm 2 In the above, the deviation of the extended thickness can be 15% or less, preferably 10% or less, and the haze can be 10% or less, preferably 8% or less.

[0046] [Measurement method]

[0047] A biaxially stretched film having a thickness of 20 μm and a width of 8 m was prepared using the resin composition under the conditions of a molding speed of 400 m / min, a five-fold longitudinal (MD) elongation and a stretching temperature of 112 to 128° C., a nine-fold transverse elongation and a stretching temperature of 108 to 116° C., and the tensile strength of the test piece of the biaxially stretched film was measured using a tensile tester (model name: Instron, 4466) under the conditions of a load cell of 100 N and a test speed of 500 mm / min according to the provisions of ASTM D882, the prepared film was cut into a length of 1 m, and the thickness was measured at any part of the eight equal parts to obtain a thickness deviation compared to before stretching, and the thickness deviation was averaged to measure the stretched thickness deviation, and the haze (Haze) of the stretched film was measured using a haze meter (model name: Nippon Denshoku, NDH5000) according to the provisions of ASTM D1003 for the test piece.

[0048] The present invention is described in more detail below by specific examples and comparative examples. In the examples and comparative examples, the density, melt flow index and CFC analysis were measured according to the following methods.

[0049] [Measurement method]

[0050] (1) Density

[0051] The measurement was performed according to ASTM D1505.

[0052] (2) Melt Index (MI)

[0053] The measurement was carried out according to ASTM D1238 at 190°C and a load of 2.16 kg.

[0054] (3) a-TREF analysis using CFC (Cross-Fractionation Chromatography)

[0055] The CFC analysis was performed in a CFC instrument from Polymer Char, Valencia, Spain. The first level of the instrument includes a TREF column, the second level includes a GPC column group, and the downstream of the GPC column includes an infrared detector (IR4 from PolyemrChar). The sample to be analyzed was stirred at 150°C for 80 minutes to dissolve it in 1,2,3-trichlorobenzene at a concentration of about 2.5 mg / ml. The solution was loaded in the center of the TREF column, stabilized at 100°C for 45 minutes, and then slowly (0.5°C / min) cooled to 35°C to crystallize the polymer. After that, the low temperature was maintained for 10 minutes, and the soluble fraction was injected into the GPC column. All GPC analyses were performed using the solvent 1,2,4-trichlorobenzene at 1 ml / min, a column temperature below 140°C and the "overlapping GPC injection" mode.

[0056] (4) Thermal characteristics

[0057] Using a differential scanning calorimeter (trade name DSC, manufactured by Perkin-Elmer Co.), 10 mg of the test piece was pre-melted at 220° C. for five minutes under a nitrogen atmosphere, and then the temperature was reduced to −100° C. at a temperature reduction rate of 5° C. / min. Then, the temperature was increased to 200° C. at a temperature increase rate of 10° C. / min, and while cooling at the same temperature reduction rate as the temperature increase rate, the glass transition temperature (Tg), melting point (Tm), and crystallization temperature (Tc) were confirmed.

[0058] Examples and Comparative Examples

[0059] The compositions shown in Table 1 and Table 2 were prepared. At this time, for the copolymer mixing composition (Examples 1 to 5, Comparative Examples 2, 3, 5 and 6), the copolymers of the corresponding combinations were put into a twin-screw extruder and melt-kneaded at 180 to 220° C. to prepare a granular polyethylene resin composition, while for Comparative Examples 1 and 4, they were prepared separately without the kneading process. For the compositions prepared according to Example 1 and Comparative Example 1, Figure 2 and Figure 3The temperature-elution fractionation curves analyzed by TREF and by temperature-increasing elution fractionation are shown respectively.

[0060] Experimental example

[0061] A biaxially stretched film having a thickness of 20 μm and a width of 8 m was prepared using the resin composition under the conditions of a molding speed of 400 m / min, a five-fold longitudinal (MD) elongation and a stretching temperature of 112 to 128° C., a nine-fold transverse elongation and a stretching temperature of 108 to 116° C., and the tensile strength of the test piece of the biaxially stretched film was measured using a tensile tester (model name: Instron, 4466) under the conditions of a load cell of 100 N and a test speed of 500 mm / min according to the provisions of ASTM D882, the prepared film was cut into a length of 1 m, and the thickness was measured at any part of the eight equal parts to obtain the thickness deviation compared to before stretching, and the thickness deviation was averaged to measure the stretched thickness deviation, and the test piece was measured using a haze meter (model name: Nippon) according to the provisions of ASTM D1003. The haze of the stretched film was measured by Denshoku, NDH5000, and the results are shown in Table 1. The stretched thickness deviation is an index indicating the stretching processability, and the case where the thickness deviation is 10% or less is indicated as "◎", the case where the thickness deviation is 15% or less is indicated as "○", the case where the thickness deviation exceeds 15% is indicated as "△", and the case where it is broken is indicated as "X".

[0062]

[0063]

[0064] Referring to Table 1, it can be confirmed that the films (Examples 1 to 5) prepared from the resin composition involved in the present invention can be biaxially stretched in a wider temperature range, and have excellent thickness smoothness and color characteristics, wherein the resin composition has a melt flow index and density within a specified range, and further has a glass transition temperature, melting point or crystallization temperature within a specified range, and is a mixture of ultra-low density polyethylene (A), linear low density polyethylene (B) and high density polyethylene (C) prepared using specific comonomers, and the resin composition exhibits a TREF weight fraction within a specified range.

[0065] In this regard, referring to Table 2, it can be confirmed that in the case of using only linear low-density polyethylene (B) (Comparative Examples 1 and 4), there are problems such as breakage during stretching or thickness deviation exceeding 15%, and the TERF weight fraction exceeds the expected value, resulting in low biaxial stretching properties.

[0066] Moreover, when the high-density polyethylene (C) was not mixed (Comparative Example 2) or the ultra-low-density polyethylene (A) was not mixed (Comparative Example 3), it was also confirmed that there were problems such as breakage during stretching or thickness deviation exceeding 15%, and the TERF weight fraction exceeded the expected value, resulting in low biaxial stretching properties.

[0067] Moreover, it was confirmed that even if copolymers A to C were mixed at the same time, when the content of high-density polyethylene (C) was too high (Comparative Example 5), due to the large amount of crystalline molecules, it was impossible to stretch during the stretching process, resulting in breakage; when the content of ultra-low-density polyethylene (A) was too high (Comparative Example 6), due to the large amount of low-crystalline molecules, the mechanical properties decreased, resulting in a decrease in the final tensile strength, and it could not be used as an actual product.

[0068] The preferred embodiments of the present invention are described in detail above. The description of the present invention is for illustration only, and a person with ordinary knowledge in the technical field to which the present invention belongs should be able to understand that other specific forms can be easily deformed without changing the technical concept or essential features of the present invention.

[0069] Therefore, the scope of the present invention is indicated by the appended claims rather than the above detailed description. All changes or modifications derived from the meaning, scope and equivalent concepts of the claims should be interpreted as being included in the scope of the present invention.

Claims

1. A polyethylene resin composition for a biaxially oriented film, wherein: By analytical temperature rising elution fractionation (a-TREF) analysis, the molecular weight of the material fractionated at a temperature below 35°C was 5-20% by weight, and the molecular weight of the material fractionated at a temperature above 94°C was 5-20% by weight.

2. The polyethylene resin composition for biaxially oriented films according to claim 1, characterized in that: The resin composition comprises: 1 to 30 wt% of copolymer A, wherein the copolymer A is a copolymer of ethylene and an olefin having 4 to 10 carbon atoms and has a density of 0.860 to 0.910 g / cm 3 ; 60 to 98 weight percent of copolymer B, wherein copolymer B is a copolymer of ethylene and an olefin having 4 to 10 carbon atoms and has a density of 0.925 g / cm 3 Above and less than 0.940g / cm 3 ;and 1 to 10% by weight of copolymer C, wherein the copolymer C is a copolymer of ethylene and an olefin having 4 to 10 carbon atoms and has a density of 0.940 to 0.970 g / cm 3 .

3. The polyethylene resin composition for biaxially oriented films according to claim 2, characterized in that: The melt flow index of the copolymer A at 190°C and 2.16kg load is 0.2-6g / 10min, the melt flow index of the copolymer B at 190°C and 2.16kg load is 1-3.5g / 10min, and the melt flow index of the copolymer C at 190°C and 2.16kg load is 0.2-2.5g / 10min.

4. The polyethylene resin composition for biaxially oriented films according to claim 3, characterized in that: The glass transition temperature Tg of the copolymer A is -50 to -45°C, the melting point Tm of the copolymer B is 120 to 130°C and the crystallization temperature Tc is 110 to 115°C, and the melting point Tm of the copolymer C is 130 to 140°C and the crystallization temperature Tc is 115 to 125°C.

5. The polyethylene resin composition for biaxially oriented films according to claim 1, characterized in that: The resin composition has a melt flow index of 1 to 3 g / 10 min and a density of 0.920 to 0.940 g / cm at 190° C. and a load of 2.16 kg. 3 .

6. The polyethylene resin composition for biaxially oriented films according to claim 1, characterized in that: The longitudinal and transverse tensile strengths of the resin composition measured under the following conditions are 700 kgf / cm 2 Above, the extension thickness deviation is less than 15%, and the haze is less than 10%. [Measurement method] A biaxially stretched film with a thickness of 20 μm and a width of 8 m was prepared using the resin composition at a molding speed of 400 m / min, a five-fold longitudinal (MD) elongation and a stretching temperature of 112 to 128° C., a nine-fold transverse elongation and a stretching temperature of 108 to 116° C., and the tensile strength of the test piece of the biaxially stretched film was measured using a tensile tester with a model name of Instron 4466 under the conditions of a load cell of 100 N and a test speed of 500 mm / min according to the provisions of ASTM D882. The prepared film was cut into a length of 1 m, and the thickness was measured at any position of eight equal parts to obtain a thickness deviation compared to before stretching, and the thickness deviation was averaged to measure the stretched thickness deviation. Moreover, the haze of the stretched film was measured using a haze meter with a model name of Nippon Denshoku NDH5000 according to the provisions of ASTM D1003 for the test piece.

Citation Information

Patent Citations

  • Polyethylene film

    KR100746253B1